Additives for polyolefins : getting the most out of polypropylene, polyethylene and TPO - Tolinski, Michael (PDL handbook series., 2009)
Additives for Polyolefins is a unique quick-reference resource for those who create or use polyethylene and polypropylene compounds-the most commercially important family of plastic materials, making up close to half of the volume all plastics produced and used. These polymers would be useless without various additives. The book focuses on polyolefin additives that are currently important in the plastics industry, alongside new additives of increasing interest, such as nanofillers and environmentally sustainable materials. As much as possible, each chapter emphasises the performance of the additives in the polymer, and the value each relevant additive brings to polypropylene or polyethylene. Where possible, similar additives are compared by capability and relative cost. In this new edition, product tables have been updated with the most current product and company names, new case studies have been added, the role of nanofillers is discussed in greater detail, and the book concludes with a discussion on blending and handling additives, along with an entirely new chapter on how engineers can approach the issue of sustainability when choosing an additive.